Approach of science, poetry and technologies in the work: «Tolo Nei. Meditations in the Dry Leaf Forest» by Gustavo Adolfo Becerra (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
This work is an approach to the latest poetry book «Tolo Nei. Meditations on the Forest of Dry Leaves», 2012 published by the Chilean poet Gustavo Adolfo Becerra in Santiago, Chile. The book is a complex body that experiments with different voices, languages, poetry, virtual technology and sciences, which is all connected. Science and poetry complements each other in the modern world and literature, they have one important thing in common: they both are representation and look for the truth. The new structure of the book, presented by the author, is explained as well as the place and meaning of the World Wide Web for the literary and artistic purposes. The work is a series of generalizations about the scientific and poetic imaginations, the use of frac-tals, hypertext, changing form of poetry in the scientific age, the new languages, the new thinking.
Keywords: poetry; science; hypertext; scientific and poetic